Enhanced identification and functional protective role of carbon nanoparticles on parathyroid in thyroid cancer surgery: A retrospective Chinese population study. Issue 46 (November 2016) - Shi, Chenlei; Tian, Bo; Li, Shengze; Shi, Tiefeng; Qin, Huadong; Liu, Shaoyan
Abstract : Abstract: The aim of this study was to determine the effects of nanocarbon particles in combination with meticulous capsular dissection on enhancing the identification and protecting the function of parathyroid glands in thyroid cancer surgery. The data of 97 patients with papillary thyroid tumors diagnosed and treated at the Second Affiliated Hospital, Harbin Medical University between January 2014 and February 2015 were reviewed. Data regarding the sex, age, calcium and parathyroid hormone (PTH) levels, tumor size, multifocality, T stage, and extrathyroid invasion were collected. The incidence of surgeries in which the parathyroid glands were cut mistakenly, the concentration of serum calcium and parathyroid hormone before surgery (baseline) and after surgery on days 1, 3, and 7, and 1 and 6 months in the patients of the two groups (the nanocarbon and control groups) were analyzed. Fifty-two patients underwent meticulous capsular dissection combined with nanocarbon treatment (nanocarbon group), and 45 underwent meticulous capsular dissection alone (control group). The nanocarbon group showed a significantly higher total and average number of revealed parathyroid glands (average number is the mean for different individuals have different number) and a lower incidence of the parathyroid glands being mistakenly cut, in addition to a lower level of hypoparathyroidism than control group following surgery ( P  < 0.05). Serum calcium and PTH levels were significantly lower in patients from both groups after surgery on days 1, 3, and 7 and after 1 month, compared with the preoperative levels ( P  < 0.05). Compared with the control group, the serum calcium and PTH levels were significantly higher in the nanocarbon group after surgery on days 1, 3, 7, than in the control group. Treatment with nanocarbon in combination with meticulous capsular dissection can significantly facilitate the identification of the parathyroid in thyroid cancer surgery, reduce the risk of mistakenly cutting the parathyroid, and reduce the incidence of postoperative hypoparathyroidism.